Defining reference values for body composition indices by magnetic resonance imaging in UK Biobank. Issue 2 (30th January 2023) - Dai, Liang; Huang, Xiao‐yan; Lu, Yue‐qi; Liu, Yu‐yang; Song, Cong‐ying; Zhang, Jing‐wen; Li, Jing; Zhang, Yue; Shan, Ying; Shi, Yu
Abstract: Background: Magnetic resonance imaging (MRI) is the gold standard for evaluating body composition. However, the reference ranges have not been established. Methods: Three lean tissue and seven adipose tissue parameters based on MRI data from the UK Biobank were used in this study. Participants with European ancestry and data on at least one parameter were screened. Age‐ and sex‐specific percentile curves were generated using the lambda–mu–sigma method. Three levels of reference ranges were provided, which were equivalent to the mean ± 1 standard deviation ( SD ), 2 SD s and 2.5 SD s. Results: The final analysis set for each parameter ranged from 4842 to 14 148 participants (53.4%–56.6% women) with a median age of 61. For lean tissue parameters, compared with those at age 45, the median total lean tissue volume and total thigh fat‐free muscle volume at age 70 were 2.83 and 1.73 L, and 3.02 and 1.51 L lower in men and women, respectively. The median weight‐to‐muscle ratios at age 45 were 0.51 and 0.83 kg/L lower compared with those at age 70 in men and women, respectively. Adipose tissue parameters showed inconsistent differences. In men, the median muscle fat infiltration, visceral adipose tissue (VAT) volume, total abdominal adipose tissue index and abdominal fat ratio were 1.48%, 0.32 L, 0.08 L/m 2 and 0.4 higher, and the median abdominal subcutaneous adipose tissue (ASAT) volume and total adipose tissue volume were 0.47 and 0.41 L lower, respectively, at age 70 than at age 45. The median total trunk fat volume was approximately 9.53 L at all ages. In women, the median muscle fat infiltration and VAT volume were 1.68% and 0.76 L higher, respectively, at age 70 than at age 45. The median ASAT volume, total adipose tissue volume, total trunk fat volume, total abdominal adipose tissue index and abdominal fat ratio were 0.35 L, 0.78 L, 1.12 L, 0.49 L/m 2 and 0.06 higher, respectively, at age 60 than at age 45. The medians of the former three parameters were 0.33 L, 0.14 L and 0.20 L lower, at age 70 than at age 60. The medians of the latter two parameters were approximately 3.64 L/m 2 and 0.55 at ages between 60 and 70. Conclusions: We have established reference ranges for MRI‐measured body composition parameters in a large community‐dwelling population. These findings provide a more accurate assessment of abnormal adipose and muscle conditions.